Antioxidant Capacity of Catnip (Nepeta cataria) - Gokce, I. (Asian Journal of Chemistry, 2010)
Antioxidants are emerging as prophylactic and therapeutic agents for various diseases. Antioxidants are important in protection against hypertension, diabetes, cardiovascular diseases and cancer. However, little is known about the antioxidant property of the extract from Nepeta cataria, a medicinally useful traditional medicinal herb. Here the antioxidant capacity of ethanolic extracts prepared from Nepeta cataria was evaluated. The present results demonstrate that Nepeta cataria extracts examined in this article exhibit antioxidant activity. This activity is correlated with the total phenolic compounds content in the extract which implicates that the Nepeta cataria extract may serve as potential natural source of antioxidants.